Optimization of an Evanescent Field Sensor based on D-Shaped Plastic Optical Fiber for Chemical and Biochemical Sensing. (2016) - Sequeira, F.; Bilro, L.; Rudnitskaya, A.; Pesavento, M.; Zeni, L.; Cennamo, N.
Abstract: The experimental investigations of the performance of a D-shaped Plastic Optical Fiber (POF) sensor are presented. The phenomenon behind this optical fiber sensor based platform is the variation of the transmitted light at the output of the POF with the external refractive index. The resolution of the optical sensing platform is strongly dependent on the length of the sensing region, decreasing from 10 -1 to 10 -3 RIU with length varying from 1cm to 5cm. The sensor production procedure is very easy, fast and low-cost. The obtained resolution allows further development for chemical and biochemical sensing by chemical receptor, e.g. molecularly imprinted polymer. A good resolution was obtained using sensing area length of 5cm.